Assessing Factors Affecting Sustainable Food Value Chain Development: A Case of the Agricultural Sector in Dong Nai Province - Tan, Nguyen Van; Tam, Phan Thanh (Social Science Learning Education Journal, 2017)
Agricultural sector plays a strategic role in the process of economic development of a developing country such as Vietnam.It has already made a significant contribution to the economic prosperity of advanced and developing countries and its role in the economic development of less developed countries is of vital importance. We can see that increase in agricultural production and the rise in the per capital income of the rural community, together with the industrialization and urbanization, lead to an increased demand in industrial production. Besides, agricultural developments are not alternatives but are complementary and are mutually supporting with respect to both inputs and outputs.The agriculture sector is the backbone of an economy which provides the basic ingredients to mankind and now raw material for industrialization. The studyresults showed that there were 400 persons (include: 200 managers of enterprises, 170 farmers, 30 experts) related to agricultural sector in Dong Nai provincewho interviewed and answered about 17 questions. The Data collected from June2016 to April 2017. This study had been analyzed Cronbachs Alpha testing used for the next research. Personsâ responses measured through an adapted questionnaire on a 5-point Likert scale (Conventions: 1: Completely disagree, 2: Disagree, 3: Normal; 4: Agree; 5: completely agree). Hard copy and online questionnaire distributed among 200.000 persons related to agricultural sector in Dong Nai province. The Data processed by SPSS 20.0.